2007
DOI: 10.1111/j.1445-6664.2007.00258.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of winter wheat (Triticum aestivum L.) and weeds to tank mixtures of 2,4‐D plus MCPA with clodinafop propargyl

Abstract: Field and greenhouse experiments were conducted in 2004 and 2005 to study weed control and the response of winter wheat to tank mixtures of 2,4-D plus MCPA with clodinafop propargyl. The field experiments were conducted at Yazd and Oroumieh, Iran, with factorial combinations of 2,4-D plus MCPA at 0, 975, and 1300 g ai ha -1 and with clodinafop propargyl at 0, 64, 80, 96, and 112 g ai ha -1 in four replications. The greenhouse experiments further evaluated the effect of these tank mixtures on weed control, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It indicates that due to reduced competition with the weeds the crops may produce more grains and this may result in higher yield. The increase in yield of wheat grown under field conditions and in greenhouse was recorded after the application of MCPA and in mixture with 2,4-D (Lisova, 2001;Baghestani et al, 2007). Though during the field studies in Canada, the reduction in wheat yield was observed after the treatment with phenoxy herbicides MCPA had a slight stimulatory effect on the content of photosynthetic pigments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It indicates that due to reduced competition with the weeds the crops may produce more grains and this may result in higher yield. The increase in yield of wheat grown under field conditions and in greenhouse was recorded after the application of MCPA and in mixture with 2,4-D (Lisova, 2001;Baghestani et al, 2007). Though during the field studies in Canada, the reduction in wheat yield was observed after the treatment with phenoxy herbicides MCPA had a slight stimulatory effect on the content of photosynthetic pigments (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pesticides, when chemically compatible, are often tank mixed and applied together to protect crops from a wide range of diseases, weeds, and/or insects. While reducing the cost and time required for pesticide applications, tank mixing can alter the response of the pests and/or the crops to certain active ingredients and the effects can be additive, synergistic, or antagonistic (1,2,9). Over the years, substantial efforts have been made to understand the interactions among pesticides in order to optimize crop management programs, with the majority of the literature devoted to the topic of insecticide‐herbicide interactions (4,9).…”
Section: Introductionmentioning
confidence: 99%